A genotypically distinct, melanic variant of Anopheles arabiensis in Sudan is associated with arid environments - Aboud, Mariam (Malar J, 2014)
BACKGROUND: Anopheles arabiensis, an important malaria vector in Sudan and other countries in sub-Saharan Africa, exhibits considerable ecological and behavioural plasticity allowing it to survive in the harsh conditions of arid regions. It has been shown that adult populations of An. arabiensis in the semi-desert habitat of western Khartoum State survive through the long dry season in a state of partial aestivation, characterized by limited feeding activity and a degree of arrested ovarian development. Anopheles arabiensis in these sites occurs in two phenotypic forms. One is large and heavily melanized, the other has the typical characteristics of An. arabiensis as found elsewhere in Africa. The extent of genetic variation in these forms was examined in widely separated locations in Sudan, including Kassala, Gedaref and the Northern States between 1998 and 1999 and 2004 and 2006. METHODS: Each mosquito specimen was identified using standard morphological keys and a species-specific PCR test. Sequence variation in a 660 bp fragment of the mtDNA ND5 coding region was examined and the extent of genetic divergence between the forms was estimated from F(ST) values using DNASP version 4.9. TCS 1.13 software was used to determine the genealogical relationships and to reflect clustering among mtDNA haplotypes. RESULTS: The melanic and normal forms were found in sympatry in Kassala, Gedaref and Khartoum states, with the melanic form commonest in the hottest and most arid areas. Both forms were encountered in the periods of study: 1998–1999, and 2004–2006. Only ten specimens of An. arabiensis were collected from the Northern State in February 2006, all of which were of the normal form. Based on the ND5 analysis, there was a marked subdivision between the normal and melanic forms (F(ST) = 0.59). Furthermore, the melanic form showed more genetic variability, as measured by haplotype diversity (0.95) compared with the normal form (0.57), suggesting larger effective population. CONCLUSIONS: This is the first demonstration of correspondent phenotypic and genetic structuring in An. arabiensis. The high level of genetic differentiation shown by the mtDNA ND5 locus suggests that the two forms may represent separate species. It is hypothesized that the melanic form is better adapted to hot and arid environments. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1475-2875-13-492) contains supplementary material, which is available to authorized users.